Simulation in healthcare systems: application in outpatient settings - Aiinparast A.; Tabibi S.J.; Shahaneghi K.; Arianejad M.B. (Payesh, 2008)
Objective(s): To define the main criteria for application of simulation in healthcare systems, especially in outpatient settings.Methods: This was a systematic review of the literature. The search involved the use of 3 keywords, namely simulation models, health care systems and outpatient services.Results: The articles were categorized into 3 main groups:- Changes in patients arrival patterns,- Changes in resource allocation methods,- Changes in service delivery processes.The findings are presented in the light of the above headings.Conclusion: Literature show that simulation can be an effective decision-making tool and it can be employed usefully to improve the performance of the health system. It should be kept in mind, however, that a proper information system must be in place to facilitate access to information and to encourage participation by simulation experts and stakeholders such as clients, service providers, and decision makers.